Health Promotion In The Work Context, Beyond A Healthy Organizational Model - Mahecha Guzmán, Mónica; Silva Urrea, Evelin Lizeth; Sáenz Blanco, Fabiola (Ingeniería Solidaria, 2020)
Introduction:This article is a product of the research “Health and Psychosocial Well-Being in Organizations: Effectiveness of positive interventions to improve working life from Positive Psychology” carried out during 2016 and 2018 at Universitat Jaume I in Spain. Problem: The changing conditions of the ecosystems, in which the organizations are immersed, correspond to the growing relationships between the different actors within and outside the organizational context. This constitutes a complex system, difficult to understand in the business context, making it difficult to act upon its structure for the generation of competitive advantages in the market, where the psycho-social construct of healthy organization is established as an emergency. Objective:To offer an alternative solution to the theoretical divergence of building positive organizations. Methodology: Development of a healthy organizational model, cellular type, based on a set of variables in which the GPTW and HERO models coincide, with the implementation of this structure, through a transit methodology that makes the objective of being the best place to work tangible. Conclusion: Establishing a healthy organizational model of cellular structure allows for the perception of the organizational context through traceable and flexible variables that respond to internal and external labor changes. Originality: The advances in relation to the psycho-social construct of the health organizations are limited due to multiple heterogeneous models, however, a homogeneous model is traced for the first time in this work, based on others that have been implemented in different entities. Limitations: Establish an evaluation of the model to accurately adjust the relationship between variables.